2017
DOI: 10.1162/jocn_a_01135
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Predictable and Unpredictable Stimuli by Inferior Temporal Cortical Neurons

Abstract: Animals and humans learn statistical regularities that are embedded in sequences of stimuli. The neural mechanisms of such statistical learning are still poorly understood. Previous work in macaque inferior temporal (IT) cortex demonstrated suppressed spiking activity to visual images of a sequence in which the stimulus order was defined by transitional probabilities (labeled as "standard" sequence), compared with a sequence in which the stimulus order was random ("random" sequence). Here, we asked whether IT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 32 publications
12
49
2
Order By: Relevance
“…factors such as attention (Larsson and Smith, 2012) and stimulus category (Kovács et al, 2013;. The present study demonstrates that repetition suppression of spiking activity and LFP power is not modulated by repetition probability in macaque IT even when the subject is attending the stimuli, faces are used, and the repetition probability modulates behavior.…”
Section: Effect Of Repetition Probability and Repetition Suppressionmentioning
confidence: 46%
See 3 more Smart Citations
“…factors such as attention (Larsson and Smith, 2012) and stimulus category (Kovács et al, 2013;. The present study demonstrates that repetition suppression of spiking activity and LFP power is not modulated by repetition probability in macaque IT even when the subject is attending the stimuli, faces are used, and the repetition probability modulates behavior.…”
Section: Effect Of Repetition Probability and Repetition Suppressionmentioning
confidence: 46%
“…This task requires the monkey to attend the stimulus content, but is unrelated to face repetitions or alternations. In the initial 58 recording sessions, we used a block length of 40 trials following previous studies (Kaliukhovich and Vogels, 2011; Kovács et al, 2013), which is twice the 20 trials used by Summerfield et al (2008). Later, we increased the number of trials to 120, reasoning that longer blocks provide more information about the repetition probabilities and thus may increase expectation-related effects.…”
Section: Orthogonal Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…4 for a recent review). Although some studies have reported that expected stimulus representations are dampened, 69,79,90,92,105,[109][110][111] others have found that this global suppression is attributable to the suppression of neurons tuned away from the expected stimulus feature, while the representation of the expected stimulus is actually sharpened c . 78,88,112 Interestingly, Marques et al 113 recently found that while backward inputs from rodent lateromedial visual area (LM) to V1 c When interpreting these results, it should be noted that these decoding analyses of global BOLD activity or singleunit responses did not segregate activity from the proposed error unit and expectation unit populations.…”
Section: Hypothesis 1: Summary and Conclusionmentioning
confidence: 99%